An Investigation of the Causal Relationship between Energy Consumption and Economic Growth: A Case Study of Vietnam - Bui, Xuan Hoi (International Journal of Energy Economics and Policy, 2020)
This article investigates the causal links between economic growth and energy consumption in Vietnam by using Vietnam's updated data in the period of 1984-2016. The error correction mechanism (ECM) is employed to detect the causal relationship in the presence of co-integration between two variables. Applying Granger's causality test within an error-correction modeling technique, we find long-run bidirectional Granger causality between energy consumption and economic activities. The source of causation in the long-run is found by the significance of the error correction terms in both directions. In the short-run, the unidirectional Granger causality running from energy consumption to economic growth is also observed. The findings provide implications for energy development strategy to ensure the sustainable economic growth in the long term for Vietnam - a rapid developing country in ASEAN region. Keywords: Energy, Economic growth, Granger's causality test, ECM, Vietnam. JEL Classifications: O13, O53, Q43 DOI: https://doi.org/10.32479/ijeep.9583